Ensino dos números racionais comparando medidas de unidade - Krug, Carbone Bruno Schmidt (2015)
This research aimed to investigate the possibility to develop the process of teaching and learning of the division of rational numbers with guided tasks in interpretation of measure. Adopted as methodology the Didactic Engineering and a didactic sequence in order to develop the work with students of High School. Participated of training sessions twelve students of one state school of Porto Barreiro city - Paran´a. The results of application of the didactic engineering suggest the importance of utilization of guided tasks in interpretation of measure, since strengthened the understanding, on the part of students, the concept of division of fractional rational numbers and contributed for them develop the comprehension of others questions associated to the concept of rational numbers, such as order, equivalence and density.